1998
DOI: 10.1111/j.1399-6576.1998.tb05158.x
|View full text |Cite
|
Sign up to set email alerts
|

The discriminating power of a risk score for postoperative vomiting in adults undergoing various types of surgery

Abstract: Score I was accurate in predicting PV in patients after most types of surgery with volatile anaesthetics, which suggests that this score might be useful for other centres as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1
16

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 19 publications
2
50
1
16
Order By: Relevance
“…A number of factors, including age, obesity, history of motion sickness or previous PONV, menstrual cycle, surgical procedure and postoperative pain, are considered to increase the incidence of PONV. 25,26 One can note that the incidence of PONV following SAB in our study is higher in both the intervention and control groups than that in the reported literature. 8,13,16 We attribute this to the major gynaecological surgery and female sex that we chose in our study as both are considered as significant risk factors for PONV in themselves.…”
Section: -11contrasting
confidence: 53%
“…A number of factors, including age, obesity, history of motion sickness or previous PONV, menstrual cycle, surgical procedure and postoperative pain, are considered to increase the incidence of PONV. 25,26 One can note that the incidence of PONV following SAB in our study is higher in both the intervention and control groups than that in the reported literature. 8,13,16 We attribute this to the major gynaecological surgery and female sex that we chose in our study as both are considered as significant risk factors for PONV in themselves.…”
Section: -11contrasting
confidence: 53%
“…11,12 Third, the patients underwent both the predictive tests and measurement of the outcome (reference standard), i.e., in this setting, the recording of PONV. Nevertheless, Sinclair, Chung and Mezei defined PONV as "any volunteered report of nausea or observed active retching or vomiting requiring antiemetics" whereas Apfel and co-workers, like their predecessors 13,14 systematically asked for and recorded any episode of nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the impact of the type of surgery among centres appears to be conflicting 5,12,15 with some studies showing no significant effect at all. 11,14 More interestingly, even if the type of surgery had a statistically significant effect, an operation independent score performed equally well as a more complex score considering the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [8,9] have shown that female gender, longer anesthesia time, general anesthesia, not smoking, use of postoperative opioids and previous PONV and/or motion sickness were associated with increased incidence and severity of PONV. Although less important, PONV may also be influenced by the type of surgery as well: strabismus correction and laparoscopic surgery especially have been described as risk factors for PONV [10,11] . Most of the previous studies that addressed the effect of gabapentin on reducing PONV incidence and severity have been performed on laparoscopic surgery procedures [1,12] .…”
Section: Discussionmentioning
confidence: 99%